SPECIFICS OF DATABASE STRUCTURE FOR STORING DIFFERENT TYPES OF INFORMATION IN INTEGRATED MONITORING SYSTEMS - POLIAHUSHKO, LIUBOV; SLIPCHENKO, VOLODYMYR; KRUSH , OLHA; RUDYK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Modern integrated monitoring systems of territories and objects, such as countries, regions, cities, districts, enterprises, or even natural resources, deal with a vast amount of diverse information. Indicators characterizing the state of these objects may differ fundamentally and have distinct components, specifics of data processing, and storage. This diversity poses a challenge for standardizing data under a single template, as it requires accommodating the peculiarities of each indicator. The creation of a unified database structure for such systems is a complex and extremely important aspect that can significantly enhance monitoring efficiency and productivity. This paper discusses the peculiarities of developing a database structure for complex monitoring systems of ecological, economic, energy, and social parameters of territories, where comprehensive analysis requires consideration of data from different fields, emphasizing the importance of creating a flexible database structure that can be easily modified. A vertical data storage principle is proposed for preserving heterogeneous information, which eliminates the problem of information redundancy and facilitates the development of a universal database structure. The proposed structure remains unchanged when adding new parameters, allowing various experts to work with the system and analyze the environmental state using different indicators, without requiring database restructuring or changes to the software modules utilizing it. A database structure for storing calculations and formulas employing the vertical data storage principle is developed and presented, aiming to increase data processing speed and reduce time spent on programming new mathematical tools and analysis. The described database structure is successfully utilized in a comprehensive eco-energetic-economic monitoring system.